Differences in DNA Methylation Patterns Between Vegans and Non-vegetarians in the AHS-2 Cohort (FS11-06-19). (13th June 2019) - Miles, Fayth; Mashchak, Andrew; Fraser, Gary
Abstract: Objectives: It is unclear how diets differing in content of animal products affect DNA methylation patterns. We sought to determine if DNA methylation patterns differed between vegans and non-vegetarians in the Adventist Health Study-2 (AHS-2) cohort. Methods: DNA methylation was profiled using the Infinium Human Methylation 450 K BeadChip in white blood cells of 137 participants in the AHS-2 cohort classified as vegan (57) or non-vegetarian (80) based on validated diet history data. Linear regression models were generated to test associations between diet pattern and methylation, where the response variable represented methylation intensity for individual CpG sites. This was repeated for sites separated into gene regions or in relation to CpG islands. CpG methylation was also averaged across each gene. The permutation-identified null distribution, false discovery rate of Storey et al was used to adjust for multiple testing. Results: A total of 53, 809 individual CpG sites were estimated to be differentially methylated (non-null). Of these, with this small sample, we could individually identify only up to 5.5% (differing by gene region) at FDR <0.05. A vegan diet was associated almost exclusively with hypomethylation of individual CpG sites. Significant CpG sites numbered 2504 within CpG islands, 749 and 13 CpG sites 0–200 base pairs or 201–1500 base pairs upstream of the transcription start site (TSS200 and TSS1500), respectively, and 51 and 458 sites falling within the 5' UTR and first exon, respectively. The greatest difference in methylation was observed for sites mapping to TSS200 and CpG islands, where methylation was 9.2% lower in vegans. No differences were found when CpG methylation was averaged to obtain a cumulative value for all sites (no FDR criterion) within each gene region. A total of 328 genes (averaging all methylation regions) were significantly hypomethylated in vegans relative to non-vegetarians at FDR <0.05. The greatest number of genes were hypomethylated when considering methylation of only CpG islands, followed by the TSS200, first exon, and TSS1500 regions. Conclusions: Our findings suggest substantial differences in methylation of CpG sites and genes, particularly in regulatory regions, between vegans and non-vegetarians, with a preponderance of hypomethylation among vegans. Funding Sources: National Institute of Health, National Cancer Institute, World Cancer Research Fund (UK).